Implementation of an Online Poster Symposium for a Large-Enrollment, Natural Science, General Education, Asynchronous Course - Weaver, Ella M.; Shaul, Kylienne A.; Lower, Brian H. (Frontiers in Education, 2022)
Asynchronous online courses are popular because they offer benefits to both students and instructors. Students benefit from the convenience, flexibility, affordability, freedom of geography, and access to information. Instructors and institutions benefit by having a broad geographical reach, scalability, and cost-savings of no physical classroom. A challenge with asynchronous online courses is providing students with engaging, collaborative and interactive experiences. Here, we describe how an online poster symposium can be used as a unique educational experience and assessment tool in a large-enrollment (e.g., 500 students), asynchronous, natural science, general education (GE) course. The course, Introduction to Environmental Science (ENR2100), was delivered using distance education (DE) technology over a 15-week semester. In ENR2100 students learn a variety of topics including freshwater resources, surface water, aquifers, groundwater hydrology, ecohydrology, coastal and ocean circulation, drinking water, water purification, wastewater treatment, irrigation, urban and agricultural runoff, sediment and contaminant transport, water cycle, water policy, water pollution, and water quality. Here we present a is a long-term study that takes place from 2017 to 2022 (before and after COVID-19) and involved 5,625 students over 8 semesters. Scaffolding was used to break up the poster project into smaller, more manageable assignments, which students completed throughout the semester. Instructions, examples, how-to videos, book chapters and rubrics were used to accommodate Students’ different levels of knowledge. Poster assignments were designed to teach students how to find and critically evaluate sources of information, recognize the changing nature of scientific knowledge, methods, models and tools, understand the application of scientific data and technological developments, and evaluate the social and ethical implications of natural science discoveries. At the end of the semester students participated in an asynchronous online poster symposium. Each student delivered a 5-min poster presentation using an online learning management system and completed peer reviews of their classmates’ posters using a rubric. This poster project met the learning objectives of our natural science, general education course and taught students important written, visual and verbal communication skills. Students were surveyed to determine, which parts of the course were most effective for instruction and learning. Students ranked poster assignments first, followed closely by lectures videos. Approximately 87% of students were confident that they could produce a scientific poster in the future and 80% of students recommended virtual poster symposiums for online courses.